2011
DOI: 10.1080/02791072.2011.629155
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Cultural Activities in Ethnic Identity Among California Native American Youth

Abstract: This study analyzed data from a large statewide sample of Native American adolescents throughout California to determine whether participation in cultural practices was associated with stronger ethnic identity. The Multigroup Ethnic Identity Measure (MEIM) scale was used to measure the ethnic identity of 945 Native American adolescents (416 male, 529 female) aged 13 – 19 across California. Respondents who participated in cultural activities including pow-wows, sweat lodge, drum group and roundhouse dance repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…Participation in cultural activities is central to many AI cultures and spiritual life to heal the mind, body and soul through the ritual process of singing and praying (Schweigman, Soto, Wright, & Unger, 2011; Unger et al, 2006). As they engage in cultural practices, youth may become more aware about how much more there is to learn about their own tribal cultural ways and what has been lost in terms of their Native languages, culture, and traditions, thereby increasing their HT thoughts (Whitbeck et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in cultural activities is central to many AI cultures and spiritual life to heal the mind, body and soul through the ritual process of singing and praying (Schweigman, Soto, Wright, & Unger, 2011; Unger et al, 2006). As they engage in cultural practices, youth may become more aware about how much more there is to learn about their own tribal cultural ways and what has been lost in terms of their Native languages, culture, and traditions, thereby increasing their HT thoughts (Whitbeck et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that exposure to tobacco at cultural activities may not be inherently risky, but participation in cultural activities can have the unfortunate effect of reminding AI youth about troubling historical events. We do not recommend that AI youth reduce their participation in cultural activities, because cultural activities have many benefits including strengthening EI (Schweigman et al, 2011), resilience (Currie et al, 2013; LaFromboise et al, 2006) and positive health outcomes (Kulis et al, 2012; Buchwald, Beals & Manson, 2000; Garroutte et al, 2003). Research has also shown the most resilient youth are those who participate in their cultural ways and traditions (LaFromboise et al, 2006; Goodkind, LaNoue, & Milford, 2010); therefore, inclusion of cultural activities within interventions can help promote and sustain the cultural ways for youth.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest resources in the community to deal with these issues were identified as tribal Elders; tribal youth; and Suquamish tribal traditions, values, beliefs, teachings, practices and stories. Given these findings and context, the key stakeholders, focus group members, and CAB members felt that the community concern about youth substance abuse should be addressed using a process that strengthened youths’ connection to their tribe and community, especially to extended family; specific mentors; and cultural activities, traditions, and values, all of which are believed to promote cultural identity (Caldwell et al, 2005; Edwards, 2003; Schweigman, Soto, Wright, & Unger, 2011). In addition, it would be important to build community connections, increase community support systems, and promote culture.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a qualitative study conducted by House, Stiffman, and Brown (2006), participants reported the an essential element of their achieving ethnic identity as an American Indian and a tribal member included the passing down of cultural and tribal knowledge (i.e., encompassing tribal history, beliefs, values, and traditions) within families through ceremonies, rituals, storytelling, and foods. Similarly, youths’ involvement in tribal cultural activities (e.g., powwows) has been directly linked with ethnic identity achievement (Schweigman, Soto, Wright, & Unger, 2011). These findings point to the relevance of parental cultural socialization among American Indian families in fostering adaptive psychological functioning and high ethnic identity among their youth.…”
Section: Interpersonal Cultural Risk and Resilience Factorsmentioning
confidence: 99%